The Effect of Insulin like Growth Factor Binding Protein 2 Gene on Kampung Chicken Growth Rate - Sri-Sudaryati; Sidadolog, J.H.P.; Wihandoyo; Artama, W.T.; Maharani, D. (International Journal of Poultry Science, 2013)
Insulin-like growth factor binding protein 2 regulates a broad spectrum of biological activities involved in growth, development and differentiation. The current study was designed to investigate the associations of IGFBP2 gene polymorphisms with the variance components and genetic parameters of four weekly intervals of growth rate (0-4, 4-8, 8-12 weeks) of the Kampung chicken that were evaluated with classical models of quantitative genetics. Thirty two females and 16 males Kampung chicken were genotyped with IGFBP2 gene using PCR-RFLP method. Retrieved 3 genotype (CC, CT and TT) and 2 alleles (C and T). The influence of average effect of the C allele was greater than T allele on a 4-8 weeks intervals of growth rate, meanwhile for the males turn into 0-4 and 8-12 weeks interval growth rate. Ratio component additive and dominant deviation to each genotype is always equal for each interval growth rate. Variance component from heterozygote nearly zero when frequency of homozygote nearly equal and ratio variance dominance were opposite to allele frequency. Narrow-sense heritability based on genetic variance component of 0-4, 4-8 and 8-12 weeks interval growth rate for female were 0.01, 0.47 and 0.87 while for male chicken were 0.94, 0.07 and 0.12, respectively. It was concluded that IGFBP 2 gene association with growth rate on 4-8 and 8-12 weeks on females but in males only effect on growth rate on 0-4 weeks.